The physiological role of orexin/hypocretin neurons in the regulation of sleep/wakefulness and neuroendocrine functions - Inutsuka, Ayumu; Yamanaka, Akihiro (Frontiers in Endocrinology, 2013)
The hypothalamus monitors body homeostasis and regulates various behaviors such as feeding, thermogenesis, and sleeping. Orexins (also known as hypocretins) were identified as endogenous ligands for two orphan G-protein-coupled receptors in the lateral hypothalamic area. They were initially recognized as regulators of feeding behavior, but they are mainly regarded as key modulators of the sleep/wakefulness cycle. Orexins activate orexin neurons, monoaminergic and cholinergic neurons in the hypothalamus/brainstem regions, to maintain a long, consolidated awake period. Anatomical studies of neural projections from/to orexin neurons and phenotypic characterization of transgenic mice revealed various roles for orexin neurons in the coordination of emotion, energy homeostasis, reward system, and arousal. For example, orexin neurons are regulated by peripheral metabolic cues, including ghrelin, leptin, and glucose concentration. This suggests that they may provide a link between energy homeostasis and arousal states. A link between the limbic system and orexin neurons might be important for increasing vigilance during emotional stimuli. Orexins are also involved in reward systems and the mechanisms of drug addiction. These findings suggest that orexin neurons sense the outer and inner environment of the body and maintain the proper wakefulness level of animals for survival. This review discusses the mechanism by which orexins maintain sleep/wakefulness states and how this mechanism relates to other systems that regulate emotion, reward, and energy homeostasis.